Interleukin‐6 signaling requires only few IL‐6 molecules: Relation to physiological concentrations of extracellular IL‐6. Issue 2 (27th February 2020) - Hansen, Morten B.
Abstract: Introduction: The aim of this study was to give quantitative insight into the number of cytokine molecules needed to activate a target cell and relate this to the physiological consequences of the amounts of cytokines typically detectable in humans. As a model system blood interleukin‐6 (IL‐6) was chosen since this cytokine is one of the most studied and clinically monitored cytokines, and because of the tools for the present investigations such as fully bioactive iodinated recombinant IL‐6, cellular cytokine binding assays, and bioassays have been thoroughly validated. Methods: The key intermediates of the basic equilibrium principles that govern cytokine binding and exchange were deduced and applied on concrete estimations of cellular and extracellular IL‐6 binding in the bloodstream based on experimental binding data and data from the literature. In parallel, in vitro cellular IL‐6 binding data was substantiated by paired measurements of IL‐6 bioactivity on IL‐6 sensitive B9 hybridoma cells. Results: Blood leucocytes and B9 cells expressed 50 to 300, 10 to 20 picomolar affinity, IL‐6 binding sites per cell and at physiological concentrations of IL‐6 less than 10 IL‐6 molecules seemed to be bound to blood cells. Nonetheless, binding off as few as four IL‐6 molecules per cell seemed to result in statistically significant bioactivity, whereas binding of 16 IL‐6 molecules triggered extensive cellular responses. Conclusion: Together, the estimations and the measurements support the notion that target cells with more than 100 bioactive cytokine receptors per cell, such as T cells and hepatocytes, are likely to be under steady and substantial cytokine‐induced endocrine activation. Abstract : The paper gives quantitative insight into the number of cytokine molecules needed to activate a target cell, and relate this to the physiological consequences of the amounts of cytokines typically detectable in humans.